THE APPLICATION OF THINK-TALK-WRITE STRATEGY TO IMPROVE THE STUDENTS’ WRITING SKILL: A CLASSROOM ACTION RESEARCH - Muhyiddin Aziz; Eda Maaliah (Politeknik Negeri Bengkalis, 2017)
Abstract: The aims of the research were: (1) To know that Think-Talk-Write Strategy can improve the students’ writing skill and (2) To describe the process of Think-Talk-Write-Strategy in improving students’ writing skill. This research was conducted at Madiun State Polytechnic at the Second Semester of English Department in the Academic Year of 2016/2017. There were 30 students which consisted of 5 males and 25 females. The qualitative and quantitative data were used in this research. The qauntitative data were taken from the scores of the pre-test and post-test of all cycles. The qualitative data were used to compare the result before and after the reseach. They were taken through the observation, interview, and questionnaire. Based on the discussion and conclusion, think-talk-write strategy is recommended to improve the writing skill. It is suitable for the Second Semester of English Department students at Madiun State Polytechnic.